National cultural specificity of the language units «cat» and «dog» in the Russian, English and German languages - J Baghana; U S Mikhailova (Polylinguality and Transcultural Practices, 2010)
The national cultural specificity of the language units «cat» and «dog» in the Russian, English and German languages is examined in this article. The universal and national specific features of semantics of the present units in the three languages are revealed in the work